ANALYSIS STUDY OF ARCHIVE EXHIBITION TITLED MENGINGAT-INGAT SANENTO YULIMAN (1941-1992) (2019) - Fadiansyah, Muhammad Hilmy; Hujatnika, Agung; Putri, Kiki Rizky Soetisna (Universitas Pakuan, 2024)
Archives in fine arts are the subject of study, namely how archives are presented in galleries or public spaces. This article examines the curatorial ideas at the Mengingat-Ingat Sanento Yuliman (1941-1992)’s exhibition held in 2019 at the Cipta II Gallery, Taman Ismail Marzuki, using a historical method approach and through an archive analysis method supported by archival theory according to Terry Cook's view. During his life, Sanento Yuliman was an Indonesian art critic where at the Mengingat-Ingat Sanento Yuliman (1941-1992)’s archive exhibition. The exhibition curator exhibited Sanento Yuliman's archives in the form of sketches, illustrations, caricatures, paintings, and objects collected personally. Through this exhibition study, the collection of archives as the subject of the exhibition presented in the Mengingat-Ingat Sanento Yuliman (1941-1992)’s exhibition provides findings that Yuliman's work is no longer just scientific work in written form. Still, various other forms of work, such as visual and illustrative works, are found in caricatures and paintings. This archival exhibition study sees the impression of Yuliman's deep appreciation of fine art so that his critical work is not just an idea that the art field can accept but a deep appreciation that comes from the ability to work, thoughts, and results of reflection that can be seen from the objects exhibited in Mengingat-Ingat Sanento Yuliman (1941-1992)’s as an archive.